Ixekizumab efficacy and safety with and without concomitant conventional disease-modifying antirheumatic drugs (cDMARDs) in biologic DMARD (bDMARD)-naïve patients with active psoriatic arthritis (PsA): results from SPIRIT-P1. Issue 2 (22nd December 2017) - Coates, Laura C; Kishimoto, Mitsumasa; Gottlieb, Alice; Shuler, Catherine L; Lin, Chen-Yen; Lee, Chin Hyok; Mease, Philip J
Abstract : Objective: To evaluate the efficacy and safety of ixekizumab alone or with concomitant conventional disease-modifying antirheumatic drugs (cDMARDs) versus placebo in patients with active psoriatic arthritis (PsA) as part of a SPIRIT-P1 subgroup analysis (NCT01695239 ). Methods: Patients were stratified by cDMARD use (concomitant cDMARDs use (including methotrexate) or none (past or naïve use)) and randomly assigned to treatment groups (ixekizumab 80 mg every 4 weeks (IXEQ4W) or every 2 weeks (IXEQ2W) or placebo). Efficacy was evaluated versus placebo at week 24 by the American College of Rheumatology criteria (ACR20/50/70), modified total Sharp score and Health Assessment Questionnaire-Disability Index (HAQ-DI). Safety was assessed according to cDMARD status. Results: Regardless of concomitant cDMARD usage, ACR20, ACR50 and ACR70 response rates were significantly higher versus placebo with IXEQ4W and IXEQ2W. The proportion of patients achieving HAQ-DI minimal clinically important difference was significantly higher versus placebo with IXEQ4W with concomitant cDMARD use and IXEQ2W, regardless of concomitant cDMARD use. Treatment-emergent adverse events (AE) were more frequent versus placebo for either ixekizumab-dosing regimen, regardless of concomitant cDMARD use. Serious AEs were not higher versus placebo, regardless of concomitant cDMARD use. Conclusion: Ixekizumab treatment improved measures of disease activity and physical function in patients with active PsA relative to placebo, when used with or without concomitant cDMARD therapy.